Local economic development – assessment of local attitudes towards conservation and tourism around Royal Belum-Temenggor Forest Complex, Perak, Malaysia - Kamarudin, Khairul Hisyam; Ngah, Ibrahim; Razak, Khamarrul Azahari (2015)

(untitled)
This paper shall present and discuss findings from an investigation of locals’ attitude toward conservation and sustainable ECT in two Orang Asli villages around Royal Belum and Temenggor Forest Complex (BTFC), Perak. Twenty respondents participated in the questionnaireguided surveys i.e. twelve and eight respondents from Semelor and Sungai Tiang respectively. The results from the questionnaire survey unveiled positive attitudes of the community towards tourism (92 per cent level of agreement) and strong support for biodiversity conservation (95 per cent level of agreement). The economic fulfilments of the household and income generation are amongst reasons given by the local for future ECT projects. New local jobs will be created and poverty addressed, as indicated by 0.95 Relative Importance Index (RII) value. Similarly, we observed RII value for environmental reason and a growing concern for protecting natural and cultural resources from overexploitation and extinction (with RII value of 0.95). This study found that benefits resulting from the protected conservation area might substantially increase local supports for better conservation. This paper conclude by putting forth two recommendations to be considered for designing and implementing more comprehensive framework and operational need for sustainable ECT and conservation namely: (1) determination of local community needs and readiness towards sustainable ECT through comprehensive and collaborative research, and (2) organisational and capacity building aimed at preparing community and their stakeholders in realising sustainable ECT development and conservation efforts in protected area.